The ‘Golden Fifties’ and the ‘tide of immorality’: Wolfgang Koeppen’s Tauben im Gras - Weber, Undine; Williams, Alison (Acta Academica: Critical views on society, culture and politics, 2009)
The struggles West Germans and African-Americans faced during the early post-World War II years of economic prosperity (the “Golden Fifties”) were compounded by confused ideologies concerning morality, sexuality and racism (“the tide of immorality”). This article provides an overview of the socio-historical background of the setting of Wolfgang Koeppen’s novel, in order to illustrate the findings with regard to the social and moral difficulties that arose from the American occupation of West Germany.